PENGARUH HYGIENE DAN KUALITAS PACKAGING TERHADAP KEPUASAN KONSUMEN DI SOP AYAM KLATEN TIBAN CENTER - Handayani, Nadya; Saputra, Eryd (JURNAL MEKAR, 2023)
At first this klaten soup had many customers, but in the following years many home-based businesses also sold chicken soup. Currently, the Klaten soup tends to be quiet. The aims of this study were (1) to determine the effect of hygiene on consumer satisfaction, (2) to determine the effect of packaging quality on consumer satisfaction, (3) to determine the effect of hygiene and packaging quality on consumer satisfaction at the Sop Klaten Tiban Center. This research is a quantitative research with a survey method. This study uses data taken from a sample of customers who answer the questionnaire. Methods of data analysis using Multiple Linear Regression Analysis. The results of this study show that: (1) hygiene affects consumer satisfaction at Sop Klaten Tiban Center (2) Packaging quality does not affect consumer satisfaction at Sop Klaten Tiban Center (3) hygiene and packaging quality affect consumer satisfaction at Sop Klaten Tiban Center. Hygiene is very important for consumer satisfaction so that it can be further improved regarding the cleanliness of the restaurant environment, and packaging also needs to be improved so that it provides more customer satisfaction, but there is no such influence so that sellers can improve in other ways, for example the taste of food.